Factors influencing purchase intention towards tablet among young adult in W.P Labuan / Norain Johari - Johari, Norain (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2015)
The purpose of this project paper is to study the factors influencing purchase intention towards tablet among young adult in W.P.Labuan. The researcher is focusing on the brand equity elements which are brand loyalty, brand awareness, brand association and perceived quality. Quantitative data collection method and the simple random sampling are used to aid the research. 152 questionnaires will be distributed to the respondents and will be analyzed by using the SPSS software. The research is conducted allocated in Labuan Town area and the places are shopping mall such as Ujana Kewangan and educational institution such as SMK Labuan.